Resin-dentin bond stability and physical characterization of a two-step self-etching adhesive system associated with TiF4 - Torres, Gabriele Barbosa; da Silva, Tânia Mara [UNESP]; Basting, Rosanna Tarkany; Bridi, Enrico Coser; França, Fabiana Mantovani Gomes; Turssi, Cecilia Pedroso; do Amaral, Flávia Lucisano Botelho; de Paiva Gonçalves, Sérgio Eduardo [UNESP]; Basting, Roberta Tarkany (Elsevier, 2017)
Objectives To evaluate the bond strength to superficial (SD) and deep (DD) dentin after the use of 2.5% (T2.5%) or 4% (T4%) titanium tetrafluoride (TiF4) in aqueous solution as a dentin pretreatment, or when incorporated into the primer (T2.5%P and T4%P) of an adhesive system (Clearfil SE Bond/CL). Degree of conversion (DC), particle size (PS), polydispersity index (PI) and zeta potential (ZP) of the solutions were evaluated. Methods Fifty molars were sectioned longitudinally to obtain two slices of each tooth, which were demarcated into SD and DD. Treatments were applied (n = 10): CL; T2.5%; T4%; T2.5%P; T4%P. After 24 h or 180 days storage, microshear bond strength tests were performed. The DC values of T2.5%P and T4%P were evaluated by FTIR. PS, PI and ZP were measured using dynamic light scattering. Results Analysis of mixed models showed significant effect of concentration of TiF4 * solution * storage time (p = 0.0075). There were higher bond strength values in SD than in DD (p = 0.0105) for all treatments in both times. The failure mode showed adhesive failures in the majority of groups, irrespective of depth and time (p = 0.3746). The bond strength values were not affected by treatments. Lower average particle size was observed for T2.5%P and T4%P at baseline. T2.5% and T4% showed a trend towards agglomeration. Significance Higher bond strength values were achieved at SD for all treatments and times. The failure modes observed were adhesive. TiF4 incorporation did not affect DC. T2.5%P and T4%P presented excellent stability over time.
Keywords: Adhesive system; Degree of conversion; Dentin; Dynamic light scattering; Hydrolytic degradation; Microshear bond strength; Titanium tetrafluoride